Case Report: Cytologic Description of Somatotroph Pituitary Adenoma in a Cat - Alonso, Flavio H.; Niedringhaus, Kevin D.; Ceregatti, Mariah G.; Maglaty, Marisa A. (Frontiers in Veterinary Science, 2022)
This case report describes for the first time the cytologic characteristics of a hormonally secreting pituitary adenoma in a cat. An 8-year-old female spayed domestic long-haired cat was referred with a previous diagnosis of hypersomatotropism and secondary diabetes mellitus 7 months prior. Clinical signs included weight loss, polyphagia, polyuria, and polydipsia. Serum insulin-like growth factor-1 was 340 nmol/L (RI: 12-92), and CT scan revealed a hypophyseal mass, and a presumptive diagnosis of acromegaly was made. A transsphenoidal hypophysectomy was performed. A fragment of the pituitary gland was subjected to a squash preparation and cytology revealed a neuroendocrine neoplasm characterized by anisokaryosis and prominent nucleoli. Additional cytologic findings included cell cohesiveness, indistinct cytoplasmic borders, nuclear crowding, molding, and fragmentation. A diagnosis of adenoma was based on a lack of histopathologic or imaging evidence of invasion. A week later, during post-surgical hospitalization, the patient worsened and died. Histopathology from a necropsy procedure revealed fibrinosuppurative meningitis as a post-surgical complication. Pituitary adenomas might have an aggressive cytologic appearance, despite a lack of histopathologic invasion or dissemination.